KEMAMPUAN MENENTUKAN UNSUR INSTRINSIK CERPEN “MERDEKA” KARYA PUTU WIJAYA PADA SISWA KELAS VII SMP KARTIKA II-2 BANDAR LAMPUNG - Nani Anggraini (LPPM STKIP PGRI Bandar Lampung, 2020)
In short story learning activities, students are not only directed to understand theories such as recognizing short story characteristics, intrinsic elements of literary work (short stories), but literary learning is directed to how students are able to find intrinsic elements contained in short stories such as, plot, setting, point of view, theme, mandate, language style, characters and others. This study used a descriptive qualitative method that was normative. The population in this study were all Grade VII Students of the Even Semester Semester SMP Kartika II-Bandar Lampung in the 2019/2020 Academic Year totaling 184 students consisting of 5 (five) classes. The sampling technique was carried out using the Stritified Proportional Random Sampling technique. Samples were taken as many as 16% of 184 students, as many as 30 students. Analysis of the ability to determine the intrinsic element of the short story